ANTIMICROBIAL POTENTIAL OF GARLIC FRESH (Allium sativum L.) AND LAKOR ONION (Allium ascalonicum L.) ON THE GROWTH OF Staphylococcus aureus - Pagaya, Joseph; Lysay, Claudia Priscia; Seumahu, Cecillia Anna (RUMPHIUS, 2021)
Garlic (Allium sativum L.) and shallot Lakor (Allium ascalonicum L.) local products are plants that are used as spices for various dishes and can be used as herbal medicine. For natural use, safe and easy to consume which can be seen through its potential as herbal medicine, a study was carried out to test the antimicrobial potential of garlic (Allium sativum L.) and Lakor shallot (Allium ascalonicum L.) juice on the growth of bacteria (Staphylococcus aureus). Lakor garlic and shallots are grated, the results of grated Lakor garlic and shallots are squeezed to produce 100% pure onion bulb juice. Lakor garlic and shallot juice was diluted with concentrations of 25%, 35%, 45%, 55%, 65%, 75%, 85% and 95%, respectively. Antimicrobial activity was tested by the diffusion method using a disk to measure the diameter of the clear zone. The results showed that garlic (Allium sativum L.) was able to inhibit the growth of Staphylococcus aureus which could be demonstrated by the clear zone diameter of 16.3 mm at a concentration of 35% and at a concentration of 65% the diameter of the clear zone exceeded the clear zone of the amoxycillin antibiotic. Lakor red onion (Allium ascalonicum L.) showed antimicrobial potential but was unable to damage the bacterial cell wall as indicated by the diameter of the clear zone of 7.7 mm at a concentration of 95%. There is potential for both onion bulbs but have different antimicrobial properties against the growth of Staphylococcus aureus.